A Study Of The Tsunami Wave Immersion Of The Coast Of Tartous Governorate - محمد سومر; محمد علاء الدين (Latakia University Journal -Engineering Sciences Series, 2023)
A tsunami is a natural coastal hazard generated in the depths of the oceans and seas as a result of an earthquake, volcanic activity, landslide, or meteorite impact. It can cause loss of life and damage to property and infrastructure, but risks can be mitigated, saving lives and property, and minimizing environmental damage. In this study, a hypothetical scenario of a tsunami event was studied and a tsunami disaster was simulated using mathematical equations to obtain values that are used as inputs in the GIS program to produce inundation maps useful in identifying areas that may be vulnerable to flooding in the event of a tsunami. As well as estimating the percentage of the submerged area from the total area. It was found that inundation was greater on low coasts and relatively less on high coasts. Where the extent of inundation along the study area varies with the change of topographical height from a few meters and may reach more than 2 km in the southern plain areas, where the percentage of the inundated area in the total area of the governorate ranges within 2%, so these maps help in understanding the potential impacts on the regions prone to immersion.